“Behold, and Say ‘Tis Well”: The Redemptive Moment in Shakespeare’s The Winter’s Tale - Hanssen, Ken R. (Studia Anglica Posnaniensia, 2018)
Exploring the structural function of time in the play and its relation to this redemptive moment, in which Hermione’s body comes to represent a translation into human terms of a Neoplatonic idea of cosmic order, reveals how the play, beyond offering an idle meditation on art and nature, articulates a profoundly moral vision of existence, and will supply a useful framework for further critical investigations of both the play itself and Shakespearean romance as a whole.